Karst-Based Geotourism in Eastern Carphatian Serbia: Exploration and Evaluation of Natural Stone Bridges - Aleksandar Antić; Nemanja Tomić; Slobodan Marković (Geoconservation Research)
The region of Carpathian Serbia is much dominated by karst terrain with numerous geological and geomorphological features, especially caves and natural stone bridges, potentially significant for geotourism development. The geotourism potential of these sites is still largely untapped. In this paper, we analyze several natural stone bridges that possess geotourism potential. These sites include Velika Vratna, Mala Vratna, Suva Vratna, Samar, Valja, Osanica and Rajska stone bridge. This study aims to identify and evaluate the current state and geotourism potential of natural stone bridges as important resources for the development of karst geotourism in Carpathian Serbia by applying the Modified Geosite Assessment Model (M-GAM). The results indicate that the Vratna River basin currently has the best-rated Main Values, but it comes short for Additional Values, especially tourism infrastructure meaning that this should be the primary focus of any future geotourism development of this site. On the other hand, Valja stone bridge has the highest Additional Values but still with plenty of room for improvement. The paper also indicates the importance of other karst features in the vicinity and their role in completing the geotourism offer of this area.